ASPEK MOTIVASI TERHADAP KINERJA PENGEMUDI TAKSI PT. BOSOWA UTAMA CORPORATION - MARYADI MARYADI (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2008)
Motivation factor such as physiological needs (X1), queit needs (X2), social need (X3), valuation needs (X4), self actualitation need (X5), and external area are influence to taxi driver performance of PT, Bosowa lJtarna Corporation. Motivation factor of social needs is very influence to taxi driver performance of PT, Bosowa Utama Corporation.